Seeing god makes me feel immoral : the role of anthropomorphic god concepts in moral emotions - Yap, Yu Xiang (2019)
Past studies have shown that people have a tendency to imbue supernatural entities like God with human mental capacities such as intentions, emotions, goals, and desires. This tendency, known as anthropomorphism, serves as a mental pillar that determines whether God is perceived as a humanlike entity or an abstract, theological entity void of humanlike qualities. Such varying construals of God have previously been found to influence an individual’s moral judgment and behaviour. The present study seeks to examine the role of God anthropomorphism in eliciting different levels of moral emotions when people are reminded of their past immorality. Specifically, it was hypothesized that reminding participants of anthropomorphic God concepts (vs. theological God concepts) would induce stronger moral emotions in them, and this effect was predicted to be stronger for religious individuals. Additionally, it was predicted that participants experiencing stronger moral emotions would engage in increased prosocial behaviour as a coping strategy for threatened immorality. Overall, the findings did not support our hypotheses. We discuss plausible reasons for the null findings and propose recommendations for future related studies.